Research on financial autonomy and financial management in public higher education - Hong, Le Thi Thu (International journal of business, economics and management, 2023)
This article examines financial autonomy and management in public higher education, focusing on its definition, significance, key factors, benefits, and challenges. It emphasizes the importance of institutions’ control over their financial resources, with factors such as revenue diversification, efficient resource allocation, strategic partnerships, and performance-based funding contributing to financial autonomy. The article discusses the benefits of financial autonomy, including increased flexibility, entrepreneurial culture, and financial sustainability, while also addressing challenges like tuition affordability, marketization concerns, and accountability issues. It explores financial resource management through budgeting, resource allocation, cost control, transparency, and revenue generation. The methods and tools for financial management encompass financial planning, performance metrics, cost analysis, risk management, and technology utilization. The article concludes by offering recommendations for Vietnam, such as strengthening financial planning, diversifying revenue sources, enhancing accountability and transparency, adopting technology, and promoting collaboration. Overall, it provides valuable insights for policymakers and institutions to effectively manage financial resources and ensure the sustainability and quality of public higher education.